Artificial Diet for the Cultivation of Eri Silkworm (Samia ricini Drury 1773) (Lepidoptera: Saturniidae) - Siti Shofa Assyifa’ul Qulbi Barid; Fathur Syahrian Ramadhani; Hari Purwanto; Hendry T.S.S.G. Saragih; Abdulrahman Saad Aldawood; Tri Rini Nuringtyas; Sukirno (Communications in Science and Technology, 2025)
The objective of this present study was to identify a suitable artificial diet formulation to support the development of eri silkworms, with castor leaves (Ricinus communis) constituting the primary ingredient. The quality of the artificial diet was evaluated using neonate larvae, comparing it to fresh castor leaves. The nutritional value was assessed by analyzing the protein content in the hemolymph of fifth-instar larvae using the Folin-Ciocalteu method and proximate analysis. The findings demonstrated that an artificial diet containing castor leaf powder during early instars, with fresh leaves being incorporated into the diet later instars, resulted in higher larval protein content. The weight of cocoon, empty cocoon, and pupa was 1.59 ± 0.05 g, 0.23 ± 0.02 g, and 1.37 ± 0.05 g, respectively. The shell ratio, female wingspan, and egg fertility were found to be 15.31 ± 0.11%, 2.42 ± 0.20 cm, and 79.2 ± 5.83 eggs, respectively. Formulation P2 exhibited the lowest larval mortality (4.23 ± 0.58%) and hemolymph protein content of 27.51 μg/mL These findings are of imperative for the cultivation of eri silk worm using artificial diet to avoid pathogen contamination and controllable nutrient content considering the early larval instar that is highly sensitive to microbes and nutrient deficiencies.